Thermal degradation of agar: Mechanism and toxicity of products. (30th October 2018) - Ouyang, Qian-Qian; Hu, Zhang; Li, Si-Dong; Quan, Wei-Yan; Wen, Li-Li; Yang, Zi-Ming; Li, Pu-Wang
Highlights: Thermal degradation process of agar was studied. The relationship between the thermal stability of agar and the strength of agar was investigated. Thermal degradation mechanism of agar was investigated. The toxicity of products of agar was investigated. The potential harm of heating agar during food processing is discussed. Abstract: The mechanism of the thermal degradation and the toxicity of the thermal degradation products of agar were studied using TG/DTA, Fourier-transform infrared spectroscopy and pyrolysis gas chromatography/mass spectrometry. It was found that the thermal degradation of agar is a single-step reaction, the thermal degradation temperature ( T 0, T p, T f ) increases with increasing gel strength ( P ) and the influence of P on the thermal degradation rate is modest. The thermal degradation of agar is an exothermic reaction, and the activation energy of the reaction increases with increasing P . In the thermal degradation, agar is first decomposed into 3, 6-anhydropyran galactopyranose and galactopyranose, then 3, 6-anhydropyran galactopyranose, and finally furyl hydroxymethyl ketone, through loop opening, dehydration and hydrogen transfer. Galactopyranose follows three degradation pathways, and its final degradation products are 3, 4-atrosan, d -allose, furfural and 5-(hydroxymethyl)-2-furancarboxaldehyde. Of the degradation products, furyl hydroxymethyl ketone, furfural, and 5-(hydroxymethyl)-2-furancarboxaldehyde show some toxicity to humans.